Remington wanted to write the parabolic equation with the three points (0,3) , (−3,2) , and (3,4) . Is this possible? What does the result mean?(1 point)

Responses

This is not possible. Since a=0, the result is a linear equation, y=13x+3.
This is not possible. Since a equals 0 , the result is a linear equation, y equals Start Fraction 1 over 3 End Fraction x plus 3 .

This is possible. The parabolic equation is y=23x2+73x+3.
This is possible. The parabolic equation is y equals Start Fraction 2 over 3 End Fraction x squared plus Start Fraction 7 over 3 End Fraction x plus 3 .

This is not possible. Since a=0, only higher degree equations can be written.
This is not possible. Since a equals 0 , only higher degree equations can be written.

This is possible. The parabolic equation is y=13x2+3.

1 answer

To determine whether it is possible to fit a parabolic equation (in the form \(y = ax^2 + bx + c\)) to three given points \((0,3)\), \((-3,2)\), and \((3,4)\), we can substitute these points into the equation to create a system of equations.

  1. For the point \((0,3)\): \[ 3 = a(0)^2 + b(0) + c \implies c = 3 \]

  2. For the point \((-3,2)\): \[ 2 = a(-3)^2 + b(-3) + c \implies 2 = 9a - 3b + 3 \] Simplifying gives: \[ 9a - 3b = -1 \quad \text{(Equation 1)} \]

  3. For the point \((3,4)\): \[ 4 = a(3)^2 + b(3) + c \implies 4 = 9a + 3b + 3 \] Simplifying gives: \[ 9a + 3b = 1 \quad \text{(Equation 2)} \]

Now we have two equations:

  1. \(9a - 3b = -1\) (Equation 1)
  2. \(9a + 3b = 1\) (Equation 2)

We can add these two equations to eliminate \(b\): \[ (9a - 3b) + (9a + 3b) = -1 + 1 \] This gives: \[ 18a = 0 \implies a = 0 \]

Substituting \(a = 0\) back into either equation will provide \(b\). Using Equation 2: \[ 9(0) + 3b = 1 \implies 3b = 1 \implies b = \frac{1}{3} \]

Thus:

  • \(a = 0\)
  • \(b = \frac{1}{3}\)
  • \(c = 3\)

The resulting equation is: \[ y = 0x^2 + \frac{1}{3}x + 3 \implies y = \frac{1}{3}x + 3 \]

This is a linear equation, meaning that, while we can fit these points with a linear function, we cannot fit them to a quadratic function (parabola). Therefore, the concluding statement is:

This is not possible. Since \(a = 0\), the result is a linear equation, \(y = \frac{1}{3}x + 3\).